POTENSI DAN KELAYAKAN KAWASAN EKOWISATA PADA BLOK PEMANFAATAN TAHURA BONTOBAHARI KABUPATEN BULUKUMBA PROVINSI SULAWESI SELATAN - -, Muthmainnah; Ikmal Saleh, Muhammad; Sribianti, Irma; Ilham, Nirwana (Jurnal Belantara, 2024)
This study aims to determine the potential and feasibility of Tahura ecotourism. This research was conducted in the ecotourism area of ​​the Bontobahari Tahura Utilization Block. The data analysis method was guided by the Guidelines for Analysis of Working Areas of Natural Tourism Objects and Attractions (ADO-ODTWA) of the Directorate General of Forest Protection and Nature Conservation of 2003 and was analyzed using scoring according to the criteria contained in the Guidelines for Analysis of Operational Areas of Operational Objects and Natural Tourist Attractions of the Directorate General of Forest Protection and Nature Conservation 2003. Calculations for each of these criteria use tabulation where the numbers obtained from the results of the assessment whose weight values ​​are guided by the Assessment of Working Areas of Natural Tourism Objects and Attractions of the Directorate General of Forest Protection and Conservation 2003. Ecotourism Feasibility Assessment Method with a predetermined value for each criterion. The potential and feasibility of Bontobahari Tahura ecotourism has the potential to be developed with a feasibility index of 84%.